A retrospective 21-year study of tumoral lip lesions - Renata da Rocha Arcoverde; Elaine Judite de Amorim Carvalho; Augusto César Leal da Silva Leonel; Danyel Elias da Cruz Pérez; Emmanoel Matheus de Oliveira Matos; Jurema Freire Lisboa de Castro (Acta Scientiarum. Health Sciences)
Lips are the location of more than 27.5% of oral lesions due to their anatomical location and constant exposure to irritating factors. The aim of the present work was to carry out a study of lip neoplasms diagnosed in an oral histopathology laboratory. This is a cross-sectional study based on secondary data of lip neoplasms diagnosed in a histopathology service between January 2000 and December 2021. 109 cases (7.6% of the total) were analyzed. The average evolution time was 26.55 months. Excisional biopsy was more frequent in 52 cases (47.7%). Males were affected in 63 cases (57.8%). The mean age was 47.07 years. Benign neoplasms were more frequent in 71 cases (65.1%), the lower lip was the main site of occurrence, with 61 cases (56%). Papilloma accounted for 33 cases (30.3%), oral squamous cell carcinoma for 32 cases (29.4%) and pleomorphic adenoma for 12 cases (11%). In 81 cases (74.3%), there was agreement between clinical diagnosis and histopathological findings. Benign neoplasms are more frequent than malignant ones, with higher incidence in males and in patients over the 5th decade of life. The most common location was the lower lip and oral squamous cell carcinoma accounted for most malignant neoplasms.